Highly integrated direct methanol fuel cell systems minimizing fuel loss with dynamic concentration control for portable applications. (September 2017) - Na, Youngseung; Zenith, Federico; Krewer, Ulrike
Abstract : Graphical abstract: Abstract : Highlights: A single material hold-up cannot simulate accurate water accumulation in a system. Volumetric inflation of anodic products disturbs water accumulation control. A highly-integrated system integrates separating and mixing process for compactness. Dynamic concentration control of methanol solution enables less evaporation. Optimal concentration can achieve high efficiency even with reduced components. Abstract: Direct methanol fuel cell (DMFC) systems are mostly composed of massive water recycling devices such as coolers, condensers or mixers even for small and light portable applications. Integrated systems, where system components serve more than one function, can be equipped with fewer components and have a lighter weight than conventional ones. However, the process integration can also bring about significant methanol evaporation in separators, resulting in low fuel efficiency. The here presented highly integrated system can minimize methanol loss with optimized concentration control to improve efficiency. Two system variants are compared with regard to concentration, temperature, water recovery controllability and efficiency. The simulation results are compared with the previously published mingled-outlet system and validated with experiments.